The Concept of Humanity and “Totalitarian Structures” in Thomas Mann’s Novella “The Law” and His Political Essays - Ilić, Goran (Anafora, 2024)
Certain literary scholars prefer the term “totalitarian structures” to more precisely describe the structures in Thomas Mann’s novella “The Law.” The application of this term in literary theory highlights the connection between the novella and the events of the time it was written, as well as the recognition of fascist and Nazi methods. Crafted in America in 1943 during Mann’s exile since 1938, the novella was compared to the German totalitarian regime, and Mann’s methods were closely tied to the rampant war events of the time. This paper explores whether the controversial terms “totalitarian structures” and “totalitarian humanity” are appropriate for a meaningful understanding of Thomas Mann’s novella “The Law.” Additionally, these terms are related to the concept of humanity that Mann formulated after Hitler’s rise to power. This paper also examines Mann’s essays that address democracy and its threats by the emergence of fascist regimes in Europe. The paper also explores relevant literary criticism studies that engage with the novella “The Law.” The main aim is to analyze the political essays of that time and compare Thomas Mann’s essays and his novella “The Law.” These analyses aim to provide a deeper understanding of his worldview and the idea of humanity of that time. To gain a deeper insight into Mann’s intentions during his work on the novella, the paper will also explore his understanding of the concepts of democracy, spirit, and freedom.